Linking Bioeconomy to Redevelopment in Contaminated Sites: Potentials and Enabling Factors - Francocci, Fedra; Trincardi, Fabio; Barbanti, Andrea; Zacchini, Massimo; Sprovieri, Mario (Frontiers in Environmental Science, 2020)
• This article proposes a bioeconomy approach to the management of contaminated sites with the aim to identify actions for the development of a common policy framework for environmental protection and sustainable development; • Among the policies addressing pollution on land and at sea, we identify four main gaps that hamper the implementation of measures for the prevention and management of contaminated sites from local to systemic scales; • We introduce three concepts from bioeconomy - i) value-chain, ii) regional perspective and iii) multi-sector approach - that are potentially conducive to socio-economic and environmental improvement of degraded areas in Europe.